Equilibrium in quantum systems of particles with magnetic interaction - Skrypnik, W. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We compute density matrices determining equilibrium states in the thermodynamic limit for a class of quantum systems. Interaction in these systems is described as a collective electromagnetic field whose scalar potential is equal to zero.